The Influence of the Motor Vehicle Tax Reduction Program and Exemption of Transfer of Title Fees on Taxpayer Compliance in the North Jakarta Region - Suharyadi, Suharyadi; Nasrullah, Nasrullah; Riyanto, Didik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the effect of the motor vehicle tax reduction program on taxpayer compliance, to determine the effect of transfer of name duty exemption on taxpayer compliance and determine the effect of the motor vehicle tax reduction program and exemption from the transfer of title fees together on taxpayer compliance in the North Jakarta area. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires. This research uses random sampling with samples108 at the SAMSAT Office in the North Jakarta area, using multiple linear regression data analysis techniques. The results of this research show that there is an influence of the motor vehicle tax whitening program on taxpayer compliance, and there is an influence of transfer of name duty exemption on taxpayer compliance and there is an influence of the motor vehicle tax reduction program and the exemption from transfer fees together on taxpayer compliance in the North Jakarta area. The variables of the motor vehicle tax reduction program and name change exemption have an influence on taxpayer compliance currently and have an influential contribution of 17,8% on the taxpayer compliance variable. It is hoped that the results of this research will contribute to further research